2019
DOI: 10.1590/1413-81232018248.22952017
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to domestic violence in women living in Istanbul and Aegean regions: a Turkish sample

Abstract: Domestic violence (DV) is a serious public health problem in the world. DV against women is also a global problem without cultural, geographic, religious, social, economic or national boundaries. This descriptive cross-sectional study was carried out to determine the situations of DV in women living in Istanbul and the Aegean Region in Turkey. The study population included outpatient clinics of state hospitals both regions. A stratified sampling by age was performed and 1100 women were included into the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
3
0
3
Order By: Relevance
“…According to the findings of the current study, violence against women is still prevalent. These results are consistent with the findings of many previous studies conducted in Turkey, which reported that the rates of violence against women varied from 30% to 70% (Aslan et al, 2019; Gencer et al, 2019; Dikmen & Gonenc, 2020). In another study, Jawarkar et al (2016) determined the prevalence of domestic violence in the form of physical, emotional, or sexual violence among 400 women in Maharashtra, India, as 40.2%.…”
Section: Discussionsupporting
confidence: 93%
“…According to the findings of the current study, violence against women is still prevalent. These results are consistent with the findings of many previous studies conducted in Turkey, which reported that the rates of violence against women varied from 30% to 70% (Aslan et al, 2019; Gencer et al, 2019; Dikmen & Gonenc, 2020). In another study, Jawarkar et al (2016) determined the prevalence of domestic violence in the form of physical, emotional, or sexual violence among 400 women in Maharashtra, India, as 40.2%.…”
Section: Discussionsupporting
confidence: 93%
“…This is due to the meeting of ideas of control and power of men over women's autonomy and the increase of violence in those who are inserted in the labor market, so at some moments it generates violence and at others it drives the exit, by the achievement of financial autonomy. 30 In this research, a tendency was observed of women with lower income to suffer more violence; however, other analyses are necessary, for the low percentage in the difference.…”
Section: Discussionmentioning
confidence: 66%
“…In seven (43.7%) [14][15][16]18,19,23,25 women's own income stood out; on the other hand, non-income can be an inhibitor for the exit of women from the relationship, for the fear of not being able to sustain themselves or their children. And highlighted in a study in Istanbul, 30 where the risk for the increase of domestic violence was related to the lower index of family income, the non-inclusion of women in the labor market and not permission by their partner.…”
Section: Discussionmentioning
confidence: 99%
“…Asadi et al, 2019; Z. S. Asadi et al, 2013; Asian et al, 2019; Barkho et al, 2011; Basar & Demirci, 2018; Daoud et al, 2017; Diop-Sidibé et al, 2006; Eldoseri et al, 2014; Elnashar et al, 2007; Ergin et al, 2005; Fageeh, 2014; Falb et al, 2019; Faramarzi et al, 2005; Ghahhari et al, 2008; Gibbs et al, 2018; Habib et al, 2011; Haj-Yahia & Clark, 2013; Hajian et al, 2014, 2018; Hamdan-Mansour et al, 2011; Jamali & Javadpour, 2016; Kaplan et al, 2011; Khayat et al, 2017; Mayda & Akkuş, 2004; Metheny & Stephenson, 2019; Moghaddam Hosseini et al, 2013; Mohammadbeigi et al, 2019; Mohammadkhani et al, 2009; Nouri et al, 2012; Oyekcin et al, 2012; Poornowrooz et al, 2019; Rahmatian & Hosseini, 2015; Ramiro et al, 2004; Saffari et al, 2017; Seedhom, 2012; Sen & Bolsoy, 2017; Tashkandi & Rasheed, 2010; Tokuç et al, 2010; Vakili et al, 2010; Vaseai et al, 2019; Vyas, 2017; Yount & Li, 2012).…”
Section: Resultsmentioning
confidence: 99%